Village-Owned Enterprises Perspectives Towards Challenges and Opportunities in Rural Entrepreneurship: A Qualitative Study with Maxqda Tools - Imam Radianto Anwar Setia Putra; Radna Andi Wibowo; Purwadi; Tania Andari; Asrori; Nisa Novia Avien Christy; Catur Wibowo Budi Santoso; Herman Yaarozatulo Harefa; Edy Suryawardana (Administrative Sciences)
The Village Fund program was started by the Indonesian government in 2015 and had a budget of USD 19.14 billion for the years 2015–2019. This research aims to provide novel insights into the importance of village-owned enterprises (BUMDes) in promoting rural entrepreneurship in rural areas of Indonesia. The investigation employs an approach that specifically emphasizes qualitative data. The individuals under investigation include the Director of the Office for Community Empowerment, Village, Population, and Civil Registration (Dispermadesdukcapil), along with five administrators/managers from BUMDes. In the “Synergy and Involvement” category, the results suggest that BUMDes are more inclined to collaborate with Small and Medium-sized Enterprises (SMEs) and other BUMDes at a similar or slightly higher level in their organizational structure rather than with large-scale companies. This is due to the fact that SMEs and other BUMDes are more inclined to have a strong and interconnected bond with each other.